The Influence of Social Media Marketing and Brand Image on Purchase Intention of Skincare Skintific in Generation Z - Hung, Agus Crisna Yanti; Oktafalia Marisa Muzammil (Dinasti International Journal of Digital Business Management, 2023)
This study aims to determine the influence of social media marketing and brand image on creative purchase intention in Generation Z. This study uses primary data, and the data used in this study were obtained. The data in this study were processed using the Structural Equation Model – Partial Least Square (SEM-PLS) version 4. This study used a sample of 111 respondents who were from Generation Z and had never used Skintific. The result of SEM-PLS analysis with the t-test and P-value ??in this study is that Social Media Marketing and Brand Image have a positive and significant effect on Purchase Intention and while there is a significant relationship between Social Media Marketing and Purchase Intention through Brand Image as a mediator.